Recensão: Kate Bailey (curator), Diva [Exhibition] (London, Victoria and Albert Museum, June 2023 – April 2024) - Cortez, Alcina (Revista Portuguesa de Musicologia, 2025)
Kate Bailey (curator), Diva [Exhibition] (London, Victoria and Albert Museum, June 2023 – April 2024)